1997
DOI: 10.1021/om970327h
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Spin−Spin Interactions across the Coordination Bond in Hexacoordinate Silicon Complexes:  Crystal-Structure Coupling Relationship

Abstract: Two-, three-, and even four-bond coupling constants are reported for the first time across the N→Si coordination bond in neutral, hexacoordinate silicon chelates. Two-bond coupling constants depend critically on bond angles, and three-bond couplings follow a Karplus-type correlation with dihedral angles obtained from X-ray crystallographic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 11 publications
(9 reference statements)
2
21
0
Order By: Relevance
“…[15] The Si±F distance in 3 corresponds well with bond lengths found in other hypervalent silicon compounds (1.60±1.73 A Ê ) [15,16]. The distances Si±O and Si±N are remarkably short compared to other hexacoordinate silicon compounds [15].…”
Section: Resultssupporting
confidence: 63%
“…[15] The Si±F distance in 3 corresponds well with bond lengths found in other hypervalent silicon compounds (1.60±1.73 A Ê ) [15,16]. The distances Si±O and Si±N are remarkably short compared to other hexacoordinate silicon compounds [15].…”
Section: Resultssupporting
confidence: 63%
“…(a) Crystallographic Structures. The preparation of complexes of the series 6 − 11 was described previously. , Figure depicts the single-crystal X-ray structures for compounds 10 and 11 . These structures have the same near-octahedral geometry reported previously for members of this series, and hence the octahedron is a characteristic geometry for this series, in contrast to 1 − 4 with the bicapped tetrahedral structure.…”
Section: Resultsmentioning
confidence: 99%
“…The structure and chemistry of hexacoordinate silicon chelates have been the focus of a number of recent studies. However, only a few structural and stereodynamic studies have been reported, and they have been described as being still in an “embryonic stage” . Within the few known crystal structures of neutral bis(N→Si) chelates, the structural diversity is rather large: most of the reported crystal structures feature a “bicapped tetrahedral” geometry ( 1 − 4 , Figure ), in which the basic tetrahedral structure around silicon is retained, with two donor nitrogens coordinated opposite two faces of the tetrahedron. By contrast, crystal structures of nearly octahedral bis(N→Si) complexes have also been reported recently ( 5 , 6 , 7 , 8 , 9 ). The factors responsible for the solid-state structures of these complexes are not yet understood.…”
mentioning
confidence: 99%
“…In DMSO- d 6 , the temperature-independent 29 Si NMR resonances for 9 and 10 appear at −141.3 and −135.2 ppm, respectively, supporting their hexacoordinate geometries. Evidence for fluoride coordination in both complexes is given by coupling with fluorine ( 1 J SiF (∼250 Hz) and 2 J CF (∼45 Hz)), which was maintained at high temperature . The NMR spectra of 9 and 10 at room temperature are more complex than those of 3 and 4 and display more than two closely spaced peaks of some of the carbon resonances of the OPO ligands.…”
Section: Synthesismentioning
confidence: 98%